Comparative analysis of non-relational and relational databases - Bui, D.B.; Ruban, N.N. (Штучний інтелект, 2016)
Relational databases (DB) provide good support for data with a predetermined structure. But the latest trends in the IT sphere have shown that the tools for working with massive data (Big Data), which have different presentations are need. Therefore, non-relational DBs (NoSQL DBs) appeared. One of the key characteristics of NoSQL DBs is that they can work with a huge range of different data structures. The article compares the most common relational and non-relational database. Реляційні бази даних (БД) забезпечують хорошу підтримку даних з наперед визначеною структурою. Але останні тренди в ІТ сфері показали, що необхідні інструменти для роботи з великими обсягами даних (Big Data), які мають різні структури представлення. Тому і з'явилися нереляційні БД (NoSQL БД). Однією з ключових характеристик NoSQL БД є те, що вони можуть працювати з величезними наборами даних різної структури. У статті порівнюються найпоширеніші реляційні і нереляційні БД.